Electrically conductive poly9butadiene-co-acrylonitrile)-polyaniline dodecylbenzenesulphonate [NBR-PAni.DBSA] blends with hydroquinone as compatibiliser - Yong K C (Journal of Rubber Research, 2012)
Blends of poly(butadiene-co-acrylonitrile) [NBR] and polyaniline dodecylbenzenesulphonate [PAni.DBSA] with electrical conductivities up to 10-1 S. cm-1, have been successfully prepared using the technique of solution mixing and casting. Compatibility of both NBR and PAni.DBSA was found to be maximised by the introduction of hydroquinone as a compatibiliser. Blends prepared with added hydroquinone exhibited the lowest electrical conductivity percolation threshold and were more conductive than the ones without any compatibiliser. Transmission electron micrographs of blends with added compatibiliser showed the lowest level of phase separation. FT-IR spectra and DSC thermal of blends with added compatibiliser also showed the largest peak and temperature shifts, respectively. These phenomenons occured due to the higher intermolecular interactions between the two blended polymers in the presence of hydroquinone.
Source Year: 2012
Keywords: Conductive rubber; Electrical conductivity; Hydroquinone; Nitrile rubber; Polyaniline